MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS PESERTA DIDIK GO ACTION COURSE DI UZBEKISTAN - Sarvar Juraboev (JPMUJ, 2025)
Mixalkha Village is a village located in the Yangiyol district, Tashkent, Uzbekistan. The background of community life in this area is very good and the surrounding community is very friendly. In terms of education, the condition of education in Mixalkha village is quite good and the learning process in surrounding schools is carried out well and conducive. However, in Mixalkha village almost all students are only fluent in the local language, namely Uzbek, and some are able to speak Russian. However, English language skills are very lacking. This is due to the lack of response and motivation from the surrounding community, including students to learn English which is considered less used in community activities. Even in schools, English lessons are less popular and not considered very important. Therefore, instilling motivation to learn and understand English is very important. By holding the Real Work Lecture (KKN) program, it is hoped that students can instill the important values ​​of having an understanding of English to the surrounding community, especially students located in Mixalkha village, Yangiyol district. The KKN activity was held at a course location, Go Action Course, which is strategically located in the middle of the village, so that local residents can see and observe the development process of students who participate in the KKN program. It is hoped that in the future the community will be more enthusiastic and motivated to learn and master English, especially in the era of globalization like today.